Effect of Motivational Interviewing on Hypertension, self-care and Quality of Life of Rural Aged People: Application of Health Belief Model - Hashem Mohamadian; Asma Bazarghani; Seyed Mahmoud Latifi; Asghar Moradgholi (Journal of Education and Community Health)
Aims: High blood pressure as a silent killer can endanger the health of the aged people. The purpose of this study was to assess the effect of motivational interviewing based on the health belief model on hypertension, self-care, and quality of life of rural aged people. Materials and Methods: This semi-experimental study without a control group, was carried out on 120 rural aged people over 60 years of age, who were covered by city health centers of Ramhormoz in 2017. The subjects were selected through the multistage random sampling method. The aged people participated in the motivational interviewing classes for 1 month each week, 2 sessions in 30-45 minutes. Data were collected using social support, perceived barriers, self-efficacy, self-care, and quality of life questionnaires, before and after the educational intervention. The data were analyzed using the Wilcoxon signed-rank test, Pearson and Filon's z test and path analysis through LISREL 8.5 and SPSS 22 software. Findings: After the educational intervention, the mean of systolic, diastolic blood pressure, and the average scores of social support, perceived barriers, self-efficacy, self-care and quality of life was improved significantly (p<0.001). Also, after the educational intervention, the variance of self-care and quality of life increased from %13 and %8 to %40 and %31, respectively. Conclusion: Motivational interviewing has led to a better explanation of the health belief model in self-care and the quality of life by modifying the mental beliefs of aged people.